2018
DOI: 10.1097/md.0000000000013725
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic impact on difference on clinical outcomes of patients with heart failure after cardiac resynchronization therapy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…A previous systematic review on this topic showed that NICM, LBBB, longer QRS, and female gender are associated with improvement in various outcomes after CRT. [21] In consonance with previous studies, [22] , [23] , [24] , [25] the present meta -analysis confirmed, with data from real-world, the importance of these clinical variables to achieve the desired left ventricular reverse remodeling with CRT.…”
Section: Discussionsupporting
confidence: 90%
“…A previous systematic review on this topic showed that NICM, LBBB, longer QRS, and female gender are associated with improvement in various outcomes after CRT. [21] In consonance with previous studies, [22] , [23] , [24] , [25] the present meta -analysis confirmed, with data from real-world, the importance of these clinical variables to achieve the desired left ventricular reverse remodeling with CRT.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, in the NICM patients who experienced ADHF, it may be related to weakness and fatigue of cardiomyocytes. The different response between ICM and NICM were also noted in HF patients with sacubitril/valsartan treatment or cardiac resynchronization therapy and provided better response of LV remodeling in the NICM population [ 28 , 29 , 30 , 31 ]. However, the mechanism was not well explored, and our results also presented that levosimendan had a different effect on mortality between the ICM and NICM populations.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent clinical trials led by Francisco [5] and Jian-Shu [34] found that ischemic cardiomyopathy is a significant predictor related to worse survival after the CRT. The underlying mechanism of this phenomenon could be explained by CRT correcting conduction disorders caused by delayed activation regions of the left ventricular wall.…”
Section: Discussionmentioning
confidence: 99%